An innovative long final year assistantship in general practice: description and evaluation. Issue 1 (2nd January 2018) - McKinley, Robert K.; Bartlett, M.; Gay, S. P.; Gibson, S.; Panesar, A.; Webb, M.
Abstract: We describe and evaluate an innovative immersive 15 week final year assistantship in general practice. Evaluation data was taken from five years of routinely collected School data and available national comparative data. The assistantship aims to enable students to consolidate knowledge and hone their skills through central participation in the care of large numbers of patients with acute and long term conditions. We estimate that most students consulted with over 450 patients during the assistantship. Students report that they became useful to their practice teams, had multiple episodes of feedback on their performance which they found useful and, in the school exit survey, reported that they were highly prepared for practice. 9.4 per cent of students reported that the assistantship was 'too long' and, especially those who completed the assistantship in the second semester, they were out of hospital for too long before F1. Some described a learning 'plateau' after the 10th week which was addressed by modifications to the assistantship. Nevertheless, in national surveys, our graduates' self-reported preparedness for practice is high, a perception shared by their F1 supervisors. General practice can make a valuable contribution to the education of senior medical students and contribute to their preparedness for practice.